Interrelation of Spirituality, Religiosity, and Competence with Madrasah Teachers’ Performance (Dinamika Ilmu, 2022)
This study aimed to examine whether spirituality, religiosity, and competence can predict teacher performance. To prove this, a study was conducted on 90 Madrasah teachers in Samarinda as the sample in this study. The research sample was selected randomly, the number of which was determined based on the Slovin formula with a precision level of 0.10 (N=867). To obtain empirical data, researchers used a questionnaire on spirituality, religiosity, competence, and teacher performance. The research data were analyzed using Multiple Linear Regression with the SPSS V26 program. The analysis results showed a significant level of p